Defining Standard Degrees to Evaluate the Physical Fitness Level for the Students of the College of Police - Naji, Ahmed; Abdul-Mohsin, Sa’oud (Journal of Physical Education, 2012)
The research aims at :-Finding standard degrees to evaluate the physical fitness evaluation for the students of the college of police.-Recognizing the standard levels of the physical fitness for the students of the college of police.The descriptive approach has been adopted for its convenience to the nature of the research. The sample consists of (200) students of an origin (800), which represents a proportion (25%) of the original community. The researchers have used the statistical processes represented by (the arithmetic mean, the standard deviation and the moderated standard degree ).The researchers have concluded the following conclusions :1.Finding standard degrees to evaluate the physical fitness levels for the students submitted to the college of police.2.Determining the standard levels for the students of the college of police.The sample subjects have achieved a good level in the tests ( abdominal exercises and frontal lending (Shnao) and long jump and endurance exercises).The subjects have not achieved the required level in the tests of speed and fitness.